Introduction to the Special Issue on Perspectives and Experiences on Mentoring Undergraduate Students in Research: Part I. Issue 3 (16th March 2017) - Hagedorn, Thomas; Li, Aihua; Rychtář, Jan; Taylor, Dewey T.
Abstract: This issue is the first of a special PRIMUS two-part issue collecting articles from experienced faculty mentors. We offer it as a valuable resource for faculty leading undergraduate research programs. It is inspired by the "Regional Faculty Workshop on REU Issues" in 2013 and the Joint Mathematics Meeting 2015 Mathematical Association of America's "Themed Session on Perspectives and Experiences on Mentoring Undergraduate Students in Research." This issue consists of seven papers focusing on the larger issues involved in creating, running, and sustaining an undergraduate research program in mathematics.